Vector median filters - Eichmann, George; Kasparis, Takis (My University, 1987)
Median filters (MF) are used both to filter ‘salt and pepper’ noise from signals and images and in other signal processing applications. In this paper, an extension of the MF, the vector median filter (VMF), is introduced. As opposed to the MF, the VMF outputs for each window location a number of data elements. By adjusting the VMF parameters, the MF is obtained as a VMF special case. Just like the MF, the VMF filters impulses while simultaneously preserving step changes in a signal. The VMF's principal advantage is that it reduces the total stored data signal computation time while it produces visual outputs comparable to that of an MF. Deterministic and statistical properties of the VMF are examined. Computer-generated experimental results are also presented.
Keywords: Electric filters; Impulse; Filters and filtration